If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(10x + -10) = 6x + 2x + -5 Reorder the terms: 5 + -1(-10 + 10x) = 6x + 2x + -5 5 + (-10 * -1 + 10x * -1) = 6x + 2x + -5 5 + (10 + -10x) = 6x + 2x + -5 Combine like terms: 5 + 10 = 15 15 + -10x = 6x + 2x + -5 Reorder the terms: 15 + -10x = -5 + 6x + 2x Combine like terms: 6x + 2x = 8x 15 + -10x = -5 + 8x Solving 15 + -10x = -5 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 15 + -10x + -8x = -5 + 8x + -8x Combine like terms: -10x + -8x = -18x 15 + -18x = -5 + 8x + -8x Combine like terms: 8x + -8x = 0 15 + -18x = -5 + 0 15 + -18x = -5 Add '-15' to each side of the equation. 15 + -15 + -18x = -5 + -15 Combine like terms: 15 + -15 = 0 0 + -18x = -5 + -15 -18x = -5 + -15 Combine like terms: -5 + -15 = -20 -18x = -20 Divide each side by '-18'. x = 1.111111111 Simplifying x = 1.111111111
| 8x+7x=46 | | 1.5(7-2x)=3x-9 | | 3(3x+5)-7=89 | | -2(3u-6)+2u=2+4(3u-1) | | x=12*log*60 | | -2x+16=4x-12 | | 5y+8=0 | | 6(7x-1)=49x | | -5(x+3)=3(x-5) | | 2(3Y-5)=15 | | 8x+11+5x-9=16-6(3-2x)+x | | 3x+2x=18 | | 5k(2+7)=3k+24 | | -6p-2(7+4p)=-98 | | 5x^3+3x^2-14x=0 | | 5(3x-20)=3(5x-1) | | 4-3/5(3a+4)=7 | | r^2-6+-3tr+2r= | | -6x+5=-3x-12 | | -3(1+4r)=-9-6r | | 17c+12=16 | | -16-10.2g=-14.g+16.85 | | t^2+3t-54= | | 4=2(x+8) | | -7(-2y+4)-6y=4(y-3)-2 | | 3y-x=-7 | | 49c^2-9= | | -3n+12=-3(n-4) | | 2y+x=2 | | -2(x+5)=-4x | | -4x-8=-280 | | 3n+4=-11+n-n |